2012
DOI: 10.1371/journal.pone.0048579
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Small RNA in Aphis gossypii and Its Potential Role in the Resistance Interaction with Melon

Abstract: BackgroundThe regulatory role of small RNAs (sRNAs) in various biological processes is an active area of investigation; however, there has been limited information available on the role of sRNAs in plant-insect interactions. This study was designed to identify sRNAs in cotton-melon aphid (Aphis gossypii) during the Vat-mediated resistance interaction with melon (Cucumis melo).Methodology/Principal FindingsThe role of miRNAs was investigated in response to aphid herbivory, during both resistant and susceptible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 63 publications
2
32
0
2
Order By: Relevance
“…These longer sRNAs were indeed also observed in the whitefly nymphs (Figure 2). A similar sRNA length distribution has previously been found in adult whiteflies (Guo et al, 2013; Wang et al, 2016) and similar sized sRNAs (between 26 and 30 nts) have been reported for other insects e.g., cotton-melon aphid ( Aphis gossypii ) or the brown planthopper ( Nilaparvata lugens ; Chen et al, 2012; Sattar et al, 2012). These longer sRNAs are assumed to be Piwi-interacting RNAs (piRNAs) and are known to be a large class of non-coding RNAs in animals, specifically linked to genome stability in germ-line cells and silence transposons (Vagin et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…These longer sRNAs were indeed also observed in the whitefly nymphs (Figure 2). A similar sRNA length distribution has previously been found in adult whiteflies (Guo et al, 2013; Wang et al, 2016) and similar sized sRNAs (between 26 and 30 nts) have been reported for other insects e.g., cotton-melon aphid ( Aphis gossypii ) or the brown planthopper ( Nilaparvata lugens ; Chen et al, 2012; Sattar et al, 2012). These longer sRNAs are assumed to be Piwi-interacting RNAs (piRNAs) and are known to be a large class of non-coding RNAs in animals, specifically linked to genome stability in germ-line cells and silence transposons (Vagin et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…Employing this approach, our study revealed 130 conserved and nine novel miRNAs from T. tabaci . The size distributions of the high‐quality reads were varied from 18 to 28 nts in our library and the peak was at the 25 nt , which was on par with previous studies (Ge et al., 2013; Liang, Feng, Zhou, & Gao, 2013; Sattar et al., 2012). Our study indicated the unique read distributes of 26–28 nts with a relative lower abundance, which is common in many small RNA libraries (Chang et al., 2016; Jagadeeswaran et al., 2010; Surridge et al., 2011; Zhang et al., 2013), indicating the presence of piRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous miRNA studies on cotton/melon aphid, A. gossypii also reported six plant miRNA family (Sattar et al., 2012). They also showed that such microRNAs were transformed into the aphid tissues (especially in gut contents) during the phloem sap ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Entre os fatores de produção que podem afetar negativamente a cultura, destaca-se o ataque de pragas de importância econômica global, como o pulgão (SATTAR et al, 2012). No Brasil, apesar de ser considerada uma praga secundária, pode ser extremamente prejudicial, pois suga a seiva das plantas, provoca enrugamento de brotações e pode transmitir vírus (GUIMARÃES; MOURA; OLIVEIRA, 2013).…”
Section: Introductionunclassified
“…Esse manejo rotacional é importante, pois o desenvolvimento de resistência do pulgão pelo uso contínuo de inseticidas já foi mencionado (SATTAR et al, 2012).…”
Section: Introductionunclassified